State of vascular wall of umbilical arteries of fetus at cytomegalovirus infection - N. N. Dorofienko (Scientific Сentre for Family Health and Human Reproduction Problems, 2015)
The paper describes the details of electron-microscopic study of the intima of blood vessels of the umbilical cord, produced during childbirth from women undergoing in the 111 trimester of gestation cytomegalovirus infection. It was found that the endothelial cells of the umbilical cord arteries there is a reduction of protein-synthetic and proliferative their functions, as well as the introduction of endothelial apoptosis, with the characteristics of manifestations, expressed degenerative and destructive changes in the cell, the loss of cell-cell contacts, intussusception plasmolemma, the destruction of the cytoskeleton, chromatin condensation, nuclear fragmentation and the formation of apoptotic bodies. Revealed changes in the endothelium may contribute dyscirculatory disorders in arterial vessels of the umbilical cord and to initiate the development of spasm of the arteries. Modification of these functions studied gestational tissues obviously contributes to the reduction of the intensity of the blood flow of the fetus, the development of intrauterine hypoxia.